Modernizing protections of traditional knowledge Batek and IPRA in digital economy notes (2022)
The passage of the Indigenous Peoples' Rights Act of 1997 paved the way for the explicit recognition and protection of indigenous peoples intellectual property rights in the Philippines. However, in spite of numerous legislation, this protection remains insufficient considering the primacy of intellectual property laws in the international arena and the exclusion of indigenous people's knowledge systems from protections granted under Philippine intellectual property laws. This inadequacy becomes more apparent when considering the challenges faced in protecting traditional knowledge in the digital economy. Considering the limited legal development in the protection of traditional knowledge in the Philippines, this paper seeks to evaluate the efficacy of the present legal framework in protecting indigenous people's traditional knowledge by analyzing existing legislation using the controversy surrounding the online platform Nas Academy's lessons on teaching the Kalinga art of tattooing (batek) to be conducted by Apo Whang-Od Oggay.
Keywords: Indigenous peoples rights act of 1997; Intellectual property rights; Traditional knowledge